Multivalent assembly of PAR-3/aPKC complexes establishes cell polarity in Caenorhabditis elegans zygotes - Sheng-Ping Hsu; Daniel J. Dickinson (Proceedings of the National Academy of Sciences, 2026)
Cell polarity is essential for the formation and function of animal tissues. Atypical protein kinase C (aPKC), its cofactor PAR-6, and scaffold protein PAR-3 regulate cell polarity in many different animal cell types. PAR-3 oligomerization is important to establish cell polarity, but how oligomerization relates to the assembly of the PAR-3/aPKC/PAR-6 complex is still unclear. Here, we use in vivo and ex vivo single-molecule techniques to demonstrate cooperativity between PAR-3 oligomerization and its binding to aPKC/PAR-6 in the Caenorhabditis elegans zygote. Using genetic perturbations, we present evidence that aPKC and PAR-6 have independent binding sites for PAR-3. We propose that multivalency drives cooperativity because a single aPKC/PAR-6 heterodimer can interact simultaneously with multiple PAR-3 molecules in an oligomer. Although single binding site mutations do not fully eliminate PAR-3/aPKC/PAR-6 binding, they do abolish anterior–posterior polarity, suggesting that PAR-3/aPKC cooperativity contributes to PAR-3 function during polarity establishment. Finally, PAR-3/aPKC cooperativity is downregulated in polarity maintenance, and this downregulation depends on the mitotic kinase PLK-1. Together, our results show how cells can developmentally regulate multivalent assembly of a key polarity complex to achieve timely segregation of cell fate determinants.